Menguji Kualitas Air Minum: Studi Bakteriologis pada Depot Air Minum Isi Ulang dan Air Minum dalam Kemasan di Pekanbaru - Hariana Etriya; May Valzon (LPPM Universitas Abdurrab, 2026)
Microbiological contamination in drinking water remains a significant public health problem associated with an increased risk of waterborne diseases, particularly infectious diarrhea. Refillable drinking water depots (Depot Air Minum Isi Ulang / DAMIU) are widely used by the community as a more economical alternative to bottled drinking water (Air Minum Dalam Kemasan / AMDK). However, the microbiological quality of DAMIU is still frequently questioned due to inadequate sanitation and suboptimal water treatment processes. This study aimed to analyze and compare the bacteriological quality of DAMIU and AMDK in Pekanbaru City based on total coliform and fecal coliform examination using the Most Probable Number (MPN) method. This analytical observational study employed a cross-sectional design. The study samples consisted of 10 drinking water samples, including 5 DAMIU samples and 5 AMDK samples selected using a random sampling technique. Microbiological examination was conducted through presumptive tests to detect total coliform and confirmed tests to identify fecal coliform. Data were analyzed descriptively and inferentially using Fisher’s exact test with a significance level of p<0.05. All DAMIU samples were contaminated with total coliform, whereas contamination was found in only two AMDK samples. The confirmed test demonstrated that two DAMIU samples were contaminated with fecal coliform, while all AMDK samples were negative for fecal coliform contamination. Fisher’s exact test showed no statistically significant difference between the bacteriological quality of DAMIU and AMDK based on presumptive test results (p=0.08) and confirmed test results (p=0.22). Conclusion the bacteriological quality of DAMIU in Pekanbaru City tended to be lower than that of AMDK, as indicated by the higher contamination of total coliform and the presence of fecal coliform in several DAMIU samples. Although no statistically significant difference was identified, DAMIU still demonstrated a higher potential risk of microbiological contamination, highlighting the need for improved sanitation monitoring and periodic water quality assessments.